Epoxy resin composite material and preparation method thereof
By pretreating and surface modification of hollow glass microbeads with boron nitride, the binding force with epoxy resin is improved, and the problem of insufficient performance of epoxy resin materials in high temperature environments is solved, and the mechanical and electrical properties of the material are improved.
Patent Information
- Application Number
- CN202411815986.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-08
AI Technical Summary
Epoxy resin materials are limited in applications in high temperature or long-term high temperature environments, and are not strong enough in terms of toughness, impact strength, high temperature resistance, etc., and the interface bonding force is weak, making it difficult to fully utilize the enhancement and toughening potential of fillers.
Hollow glass microbeads and boron nitride are used as fillers, and pretreatment and surface modification are carried out through technical means such as acetone impregnation, coupling agent modification, plasma bombardment, etc. to enhance the binding force between the filler and epoxy resin.
It significantly improves the mechanical and electrical properties of epoxy resin composites, enhances its toughness, impact strength and high temperature resistance, and improves electrical insulation and fire resistance.
Smart Images

Figure CN119775717A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an epoxy resin composite material and a preparation method thereof. Background Art
[0002] The field of polymer materials, as a key branch of materials science and technology, has been widely infiltrated into all walks of life and has had a profound impact on people's production and lifestyle. In this field, epoxy resins, with their unique advantages, including excellent mechanical properties, outstanding adhesion properties, stable chemical resistance, excellent electrical insulation and flexible processing and molding, have occupied a pivotal position in many high-tech fields such as automobiles, power electronics, and aerospace. However, while epoxy resin materials have demonstrated their strong application capabilities, they have also exposed their inherent limitations, including low toughness of cured materials, insufficient impact strength, weak flame retardancy, and limited high temperature resistance. These shortcomings have greatly limited the application of epoxy resins in high temperature or long-term high temperature and insulation-required working environments, which in turn hinders its expansion in higher-level technical fields. Therefore, exploring and developing new technologies to improve the toughness of epoxy resins, enhance impact strength, improve high temperature resistance, maintain electrical insulation, strengthen fire resistance, and optimize sound insulation has become the focus of current scientific research.
[0003] Hollow exfoliated microspheres are light, high in strength, and have good heat resistance and insulation. Flake boron nitride has excellent insulation, thermal conductivity, and heat resistance. Therefore, modifying epoxy resin by introducing fillers such as hollow microspheres and flake boron nitride to form a composite material is an effective solution and is expected to open up a new path for improving the performance of epoxy resin.
[0004] In composite materials, the interface connects the matrix and the reinforcement. On the one hand, it is responsible for effectively transferring the externally applied force from the matrix to the reinforcement, thereby exerting the mechanical properties of the reinforced material. On the other hand, the interface also plays a role in slowing down the crack propagation rate. If the interface performance is poor, the risk of delamination failure of the composite material will be greatly increased. When hollow microspheres and flake fillers are used to strengthen resin-based composites, because the surface of the hollow microspheres and flake fillers is very smooth and lacks active groups, their interfacial bonding with epoxy resin is relatively weak, making it difficult to fully exert their reinforcement and toughening potential.
[0005] At present, the main method to enhance the interfacial bonding strength is to modify the surface of the filler. The common chemical treatment process, although it improves the key properties of the filler such as surface roughness and interfacial shear strength, may bring the risk of surface corrosion, introduce unnecessary defects, and thus weaken the mechanical properties of the material. In addition, the process also consumes a lot of water resources and chemicals, which puts a certain burden on the environment. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an epoxy resin composite material.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0010] After the hollow glass microspheres and boron nitride are impregnated with acetone, vacuum drying is performed to obtain pretreated hollow glass microspheres and boron nitride;
[0011] The pretreated hollow glass microspheres are added to a mixed solution of a coupling agent and anhydrous ethanol for immersion to obtain hollow glass microspheres modified by the coupling agent, and the pretreated boron nitride is added to a mixed solution of a coupling agent and anhydrous ethanol for shear dispersion treatment to obtain boron nitride modified by the coupling agent;
[0012] After the hollow glass microspheres and boron nitride modified by the coupling agent are dried, plasma bombardment is performed on their surfaces to obtain the modified hollow glass microspheres and boron nitride;
[0013] Epoxy resin, curing agent, modified hollow glass microspheres and boron nitride are shear-dispersed to obtain a uniform blending system;
[0014] The mixed system is vacuum degassed to obtain a slurry, which is then injected into a mold and cured at a constant temperature to obtain an epoxy resin composite material;
[0015] The curing agent is added in an amount of 10-40 wt % relative to the epoxy resin, the hollow glass microspheres are added in an amount of 0.1-50 wt % relative to the epoxy resin, and the boron nitride is added in an amount of 0.1-10 wt % relative to the epoxy resin.
[0016] As a preferred solution of the method for preparing the epoxy resin composite material of the present invention, wherein: the average diameter of the hollow glass microspheres is 10 to 80 μm.
[0017] As a preferred solution of the method for preparing the epoxy resin composite material of the present invention, the boron nitride is hexagonal and has a particle size of 1 to 20 μm.
[0018] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the hollow glass microspheres are immersed in acetone for 10 to 30 hours.
[0019] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the vacuum drying temperature is 50 to 80° C. and the time is 10 to 30 hours.
[0020] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the silane coupling agent includes one or more of KH550, KH560, KH570, KH172, Z-6011, KBM-903, DL411, NDZ-201, and metal composite coupling agents.
[0021] As a preferred solution of the method for preparing the epoxy resin composite material of the present invention, the concentration of the coupling agent in the mixed solution of the coupling agent and anhydrous ethanol is 0.1-50wt%.
[0022] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the pretreated hollow glass microspheres are immersed in the mixed solution of the coupling agent and anhydrous ethanol for 2 to 10 hours at a temperature of 30 to 60°C.
[0023] As a preferred embodiment of the preparation method of the epoxy resin composite material described in the present invention, the pretreated boron nitride is sheared and dispersed in a mixed solution of the coupling agent and anhydrous ethanol for 1 to 10 hours, at a temperature of 30 to 60° C. and at a rotation speed of 2000 to 20000 rpm / min.
[0024] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the temperature for drying the coupling agent-modified hollow glass microspheres and boron nitride is 60-120°C.
[0025] As a preferred embodiment of the method for preparing the epoxy resin composite material described in the present invention, the working atmosphere of the plasma bombardment includes one or more of nitrogen, oxygen, air, hydrogen or carbon dioxide, the gas flow rate is 10 to 100 mL / min, the vacuum degree is 1 to 500 Pa, and the power is 200 to 600 W.
[0026] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the plasma bombardment time is 900 to 3600 seconds.
[0027] As a preferred embodiment of the preparation method of the epoxy resin composite material of the present invention, the epoxy resin, curing agent, modified hollow glass microspheres and boron nitride are sheared and dispersed at a speed of 2000 to 4000 rpm / min for a time of 2 to 12 minutes.
[0028] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the vacuum degassing temperature of the blending system is 25 to 40° C. and the time is 10 to 30 minutes.
[0029] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the temperature of the constant temperature curing is 30-90°C.
[0030] As a preferred embodiment of the method for preparing the epoxy resin composite material of the present invention, the constant temperature curing time is 3 to 9 hours.
[0031] Beneficial effects of the present invention:
[0032] (1) The present invention uses hollow glass microspheres, which have ultra-low density, excellent strength and outstanding insulation properties, opening up a new path for the lightweight design of epoxy resin composite materials. For boron nitride, a filler with a multi-layer stacked structure, the present invention innovatively uses a coupling agent-assisted shear stripping and surface modification technology, which can achieve effective stripping of boron nitride under the action of a coupling agent and simultaneously increase the content of active groups on its surface. Subsequently, combined with plasma treatment, the active sites on the surface are further activated and increased, making the bond between boron nitride and epoxy resin tighter, thereby significantly improving the overall insulation performance of the composite material.
[0033] (2) By finely controlling the process details of plasma treatment and optimizing the modification process of the coupling agent, the dispersion uniformity of the filler and its bonding efficiency in the epoxy resin matrix are significantly improved, thus giving the composite material excellent mechanical and electrical properties.
[0034] (3) In order to maximize its effectiveness and avoid surface defects that may be caused by plasma treatment, thereby weakening the enhancement effect, the present invention adopts the concept of coupling agent pretreatment followed by plasma fine surface modification. This concept not only effectively protects the surface structure of the glass microspheres and reduces their cracking during subsequent processing, but also greatly enhances the interaction between the filler and the epoxy resin matrix by introducing more active groups. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0036] Figure 1 is a flow chart of the preparation of the epoxy resin composite material in Example 1 of the present invention;
[0037] Figure 2 This is a scanning electron microscope image (SEM) of the epoxy resin composite material prepared in Example 1 of the present invention;
[0038] Figure 3 This is a scanning electron microscope image (SEM) of the epoxy resin composite material prepared in Example 2 of the present invention;
[0039] Figure 4 This is a scanning electron microscope image (SEM) of the epoxy resin composite material prepared in Example 3 of the present invention;
[0040] Figure 5 This is a scanning electron microscope image (SEM) of the epoxy resin composite material prepared in Comparative Example 1 of the present invention;
[0041] Figure 6 This is a scanning electron microscope image (SEM) of the epoxy resin composite material prepared in Comparative Example 2 of the present invention;
[0042] Figure 7 This is a scanning electron microscope (SEM) image of the epoxy resin composite material prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0044] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0045] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0046] The curing agent used in the present invention is an aliphatic amine curing agent with a brand name of 593, and the epoxy resin contains at least two ethylene oxide groups with a brand name of E44.
[0047] Example 1
[0048] This embodiment provides a method for preparing an epoxy resin composite material, specifically:
[0049] (1) hollow glass microspheres and boron nitride are placed in an acetone solution, immersed for 20 hours, and then vacuum dried at 70° C. for 10 hours to obtain pretreated hollow glass microspheres and boron nitride;
[0050] (2) adding the pretreated hollow glass microspheres to a mixed solution of 30% KH550 coupling agent and anhydrous ethanol, immersing at 40°C for 6 hours to obtain hollow glass microspheres modified by the coupling agent, and adding the pretreated boron nitride to a mixed solution of 30% KH550 coupling agent and anhydrous ethanol, and shearing and dispersing at 40°C at 10000 rpm / min for 4 hours to obtain boron nitride modified by the coupling agent;
[0051] (3) After drying the hollow glass microspheres and boron nitride modified by the coupling agent, the surfaces were subjected to plasma bombardment for 3600 s under the conditions of a vacuum degree of 500 Pa and a power of 500 W to obtain the modified hollow glass microspheres and boron nitride, wherein the working gas for the plasma treatment was nitrogen and the gas flow rate was 100 mL / min;
[0052] (4) By weight, take 100 parts of epoxy resin, 25 parts of curing agent, and 20 parts of a particle size of 25 μm and a true density of 0.30 g / cm 3 The modified hollow glass microspheres and 5 parts of modified boron nitride were stirred in a shear disperser at a speed of 3000 rpm / min for 10 minutes to finally obtain a uniform blending system;
[0053] (5) The blended system was evacuated at 30°C for 20 minutes to obtain a slurry from which bubbles and volatile substances were removed. The slurry was injected into a mold and then cured at a constant temperature of 60°C for 6 hours to finally obtain a hollow glass microsphere / boron nitride / epoxy resin composite material.
[0054] Example 2
[0055] This embodiment provides a method for preparing an epoxy resin composite material, specifically:
[0056] (1) hollow glass microspheres and boron nitride are placed in an acetone solution, immersed for 15 hours, and then vacuum dried at 70° C. for 10 hours to obtain pretreated hollow glass microspheres and boron nitride;
[0057] (2) adding the pretreated hollow glass microspheres to a mixed solution of 30% KH550 coupling agent and anhydrous ethanol, immersing at 40°C for 6 hours to obtain hollow glass microspheres modified by the coupling agent, and adding the pretreated boron nitride to a mixed solution of 30% KH550 coupling agent and anhydrous ethanol, and shearing and dispersing at 40°C at 10000 rpm / min for 4 hours to obtain boron nitride modified by the coupling agent;
[0058] (3) After drying the hollow glass microspheres and boron nitride modified by the silane coupling agent, the surfaces were subjected to plasma bombardment for 1800 s under the conditions of a vacuum degree of 500 Pa and a power of 500 W to obtain the modified hollow glass microspheres and boron nitride, wherein the working gas for the plasma treatment was nitrogen and the gas flow rate was 100 mL / min;
[0059] (4) By weight, take 100 parts of epoxy resin, 25 parts of curing agent, and 20 parts of a particle size of 25 μm and a true density of 0.30 g / cm 3 The modified hollow glass microspheres and 5 parts of modified boron nitride were stirred in a shear disperser at a speed of 3000 rpm / min for 10 minutes to finally obtain a uniform blending system;
[0060] (5) The blended system was evacuated at 30°C for 20 minutes to obtain a slurry from which bubbles and volatile substances were removed. The slurry was injected into a mold and then cured at a constant temperature of 60°C for 6 hours to finally obtain a hollow glass microsphere / boron nitride / epoxy resin composite material.
[0061] Example 3
[0062] This embodiment provides a method for preparing an epoxy resin composite material, specifically:
[0063] (1) hollow glass microspheres and boron nitride are placed in an acetone solution, immersed for 10 hours, and then vacuum dried at 70° C. for 10 hours to obtain pretreated hollow glass microspheres and boron nitride;
[0064] (2) adding the pretreated hollow glass microspheres to a mixed solution of 20% KH550 coupling agent and anhydrous ethanol, immersing at 40°C for 3 hours to obtain coupling agent-modified hollow glass microspheres, and simultaneously adding the pretreated boron nitride to a mixed solution of 20% KH550 coupling agent and anhydrous ethanol, shearing and dispersing at 40°C at 10000 rpm / min for 4 hours to obtain coupling agent-modified boron nitride;
[0065] (3) After drying the hollow glass microspheres and boron nitride modified by the silane coupling agent, the surfaces were subjected to plasma bombardment for 900 s under the conditions of a vacuum degree of 500 Pa and a power of 500 W to obtain the modified hollow glass microspheres and boron nitride, wherein the working gas for the plasma treatment was nitrogen and the gas flow rate was 100 mL / min;
[0066] (4) By weight, take 100 parts of epoxy resin, 25 parts of curing agent, and 20 parts of a particle size of 25 μm and a true density of 0.30 g / cm 3 The modified hollow glass microspheres and 5 parts of modified boron nitride were stirred in a shear disperser at a speed of 3000 rpm / min for 10 minutes to finally obtain a uniform blending system;
[0067] (5) The blended system was evacuated at 30°C for 20 minutes to obtain a slurry from which bubbles and volatile substances were removed. The slurry was injected into a mold and then cured at a constant temperature of 60°C for 6 hours to finally obtain a hollow glass microsphere / boron nitride / epoxy resin composite material.
[0068] Comparative Example 1
[0069] The difference between this comparative example and Example 2 is that the plasma bombardment treatment in step (3) is not performed, and the remaining preparation processes are the same as those in Example 2 to obtain the hollow glass microsphere / boron nitride / epoxy resin composite material of this comparative example.
[0070] Comparative Example 2
[0071] The difference between this comparative example and Example 2 is that the plasma bombardment time in step (3) is 300 s, and the rest of the preparation process is the same as that in Example 2, to obtain the hollow glass microsphere / boron nitride / epoxy resin composite material of this comparative example.
[0072] Comparative Example 3
[0073] The difference between this comparative example and Example 1 is that the plasma treatment time of the hollow exfoliation microbeads in step (3) is 4800s, and the rest of the preparation process is the same as that in Example 1, to obtain the hollow glass microbead / boron nitride / epoxy resin composite material of this comparative example.
[0074] The epoxy resin composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for morphology. The results are as follows: Figures 2 to 7 shown.
[0075] The mechanical properties of the epoxy resin composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1.
[0076] Table 1 Comparison of mechanical properties of epoxy resin composites
[0077]
[0078]
[0079] Depend on Figures 2 to 7 As shown in Table 1, when the plasma treatment time does not exceed 3600s, as the plasma bombardment treatment time increases, the bond between the hollow glass microspheres and the epoxy resin becomes stronger and stronger, and the tensile strength of the composite material gradually increases. This may be due to the increase in the bombardment treatment time, which gradually increases the surface roughness of the hollow glass microspheres. Figure 3 It can be seen that when the plasma bombardment time is 1800s, the microbeads coated with resin bulge, indicating that the bonding force between the microbeads and the epoxy resin is enhanced. Compared with 900s, the tensile strength of the composite material is improved.
[0080] from Figure 2 It can be seen that when the plasma bombardment lasts for 3600s, the microbeads are almost not broken due to the extremely uneven surface. Due to the protection of the coupling agent, the microbeads are closely bonded to the epoxy resin due to the highly roughened surface, and the tensile strength of the obtained composite material reaches 141.6MPa. Figure 7 It can be seen that when the plasma bombardment time is too long, the surface defects of the hollow glass microspheres increase, which can easily cause breakage and reduce the tensile strength of the composite material.
[0081] And from Figure 5 As can be seen from Table 1, due to the clean and smooth surface, the interface bonding between the microbeads without plasma treatment and the epoxy resin is relatively weak, and the tensile strength of the composite material is only 110.2 MPa.
[0082] In summary, when the plasma treatment time is 3600s, the interface bonding between the microbeads and the epoxy resin is optimal, and the mechanical properties of the prepared epoxy resin composite material are the best.
[0083] Comparative Example 4
[0084] The difference between this comparative example and Example 3 is that the modified hollow glass microspheres are not added in step (4), and the rest of the preparation process is the same as that of Example 2 to obtain the boron nitride / epoxy resin composite material of this comparative example.
[0085] Comparative Example 5
[0086] The difference between this comparative example and Example 3 is that the hollow glass microspheres in step (2) are not impregnated with KH550 coupling agent, and the rest of the preparation process is the same as that of Example 2 to obtain the hollow glass microsphere / boron nitride / epoxy resin composite material of this comparative example.
[0087] Comparative Example 6
[0088] The difference between this comparative example and Example 3 is that the boron nitride in step (3) is not subjected to plasma bombardment treatment, and the rest of the preparation process is the same as that of Example 3 to obtain the hollow glass microsphere / boron nitride / epoxy resin composite material of this comparative example.
[0089] Comparative Example 7
[0090] The difference between this comparative example and Example 3 is that the hollow glass microspheres in step (2) are not impregnated with KH550 coupling agent, and boron nitride is not added in step (4), thereby obtaining the hollow glass microsphere / epoxy resin composite material of this comparative example.
[0091] The epoxy resin composite materials prepared in Comparative Examples 4 to 7 were tested for mechanical properties. The results are shown in Table 2.
[0092] Table 2 Effects of different preparation methods on the mechanical properties of epoxy resin composites
[0093]
[0094] Comparing Comparative Examples 4, 5 and 7 with Example 3, it can be seen that the composite material needs to add hollow glass microspheres modified by coupling agents to make the composite material have better mechanical properties, and not adding boron nitride will lead to worse mechanical properties of the composite material. According to Table 2, the tensile strength of the epoxy resin can be improved by combining appropriate coupling agent treatment and plasma bombardment.
[0095] Example 4
[0096] This embodiment provides a method for preparing an epoxy resin composite material. The particle size of the microbeads in step (4) of Example 1 is adjusted to 80 μm, and the remaining preparation process is the same as that of Example 1 to obtain the hollow glass microbead / boron nitride / epoxy resin composite material of this embodiment.
[0097] The mechanical properties of the epoxy resin composite material prepared in Example 4 were tested, and the results are shown in Table 3.
[0098] Table 3 Effect of hollow glass microsphere particle size on the mechanical properties of composite materials
[0099]
[0100] Comparing Examples 1 and 4 in Table 3, it is found that the increase in particle size will limit the ability of hollow glass microspheres to reinforce epoxy resin, indicating that a composite material with better mechanical properties can only be prepared when the particle size of the hollow glass microspheres is appropriate.
[0101] In summary, the present invention adopts a coupling agent-assisted shear stripping and surface modification technology. Under the action of the coupling agent, the boron nitride is effectively stripped and the content of active groups on its surface is simultaneously increased. Subsequently, combined with plasma treatment, the active sites on the surface are further activated and increased, so that the bond between boron nitride and epoxy resin is tighter, thereby improving the overall insulation performance of the composite material.
[0102] By finely controlling the process details of plasma treatment and optimizing the modification process of the coupling agent, the dispersion uniformity of the filler and its bonding efficiency in the epoxy resin matrix are significantly improved, thus giving the composite material excellent mechanical and electrical properties.
[0103] The present invention adopts a method of first pre-treating with a coupling agent and then performing plasma fine surface modification, thereby avoiding surface defects that may be caused by plasma treatment, effectively protecting the surface structure of the glass microbeads, reducing their cracking during subsequent processing, and greatly enhancing the interaction between the filler and the epoxy resin matrix by introducing more active groups.
[0104] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an epoxy resin composite material, characterized in that: include, The hollow glass microspheres and boron nitride are impregnated with acetone respectively, and then vacuum dried to obtain pretreated hollow glass microspheres and boron nitride; The pretreated hollow glass microspheres are added to a mixed solution of a coupling agent and anhydrous ethanol for immersion to obtain hollow glass microspheres modified by the coupling agent, and the pretreated boron nitride is added to a mixed solution of a coupling agent and anhydrous ethanol for shear dispersion treatment to obtain boron nitride modified by the coupling agent; After the hollow glass microspheres and boron nitride modified by the coupling agent are dried, plasma bombardment is performed on their surfaces to obtain the modified hollow glass microspheres and boron nitride; Epoxy resin, curing agent, modified hollow glass microspheres and boron nitride are shear-dispersed to obtain a uniform blending system; The mixed system is vacuum degassed to obtain a slurry, which is then injected into a mold and cured at a constant temperature to obtain an epoxy resin composite material; The curing agent is added in an amount of 10-40 wt % relative to the epoxy resin, the hollow glass microspheres are added in an amount of 0.1-50 wt % relative to the epoxy resin, and the boron nitride is added in an amount of 0.1-10 wt % relative to the epoxy resin.
2. The method for preparing the epoxy resin composite material according to claim 1, wherein: The average diameter of the hollow glass microspheres is 10 to 80 μm.
3. The method for preparing the epoxy resin composite material according to claim 2, wherein: The hollow glass microspheres are immersed in acetone for 10 to 30 hours.
4. The method for preparing the epoxy resin composite material according to claim 1, wherein: The concentration of the coupling agent in the mixed solution of the coupling agent and anhydrous ethanol is 0.1-50 wt %.
5. The method for preparing the epoxy resin composite material according to any one of claims 1 or 4, characterized in that: The pretreated hollow glass microbeads are immersed in the mixed solution of the coupling agent and anhydrous ethanol for 2 to 10 hours at a temperature of 30 to 60°C.
6. The method for preparing the epoxy resin composite material according to any one of claims 1 or 4, characterized in that: The pretreated boron nitride is sheared and dispersed in a mixed solution of the coupling agent and anhydrous ethanol for 1 to 10 hours at a temperature of 30 to 60° C. and a rotation speed of 2000 to 20000 rpm / min.
7. The method for preparing the epoxy resin composite material according to claim 1, wherein: The plasma bombardment time is 900 to 3600 seconds.
8. The method for preparing the epoxy resin composite material according to claim 1, wherein: The epoxy resin, curing agent, modified hollow glass microspheres and boron nitride are sheared and dispersed at a rotation speed of 2000-4000 rpm / min for 2-12 minutes.
9. The method for preparing the epoxy resin composite material according to claim 1, wherein: The temperature of the constant temperature curing is 30-90°C.
10. The method for preparing the epoxy resin composite material according to claim 9, characterized in that: The constant temperature curing time is 3 to 9 hours.